Timing of post-glacial reinhabitation and ecological development of two New England, USA, drainages based on trace fossil evidence - Benner, Jacob S.; Ridge, John C.; Knecht, Richard J. (Palaeogeography Palaeoclimatology Palaeoecology, 2009)
Trace fossils as paleoecological and paleobiogeographical tools in Pleistocene glaciolacustrine sediments have been largely ignored. Combining high resolution varve stratigraphy with trace fossil data can lead to refined paleoenvironmental interpretations during times of rapid climate change. Based on trace fossils from glaciolacustrine varves in the Connecticut and Merrimack River valleys, a new timeline for the reinhabitation of New England by fish and associated invertebrates has been constructed. In addition, it appears that colonization of the recently deglaciated environments occurred in at least four successional stages. If these stages can be recognized elsewhere, it may be possible to accurately model other postglacial migrations using trace fossils and varve chronostratigraphy. (C) 2008 Elsevier B.V. All rights reserved.
id: 2035; PT: J; UT: WOS:000264010000007